THE RELATIONSHIP BETWEEN ACTIVE MOBILIZATION DURING THE FIRST STAGE OF LABOR AND THE DURATION OF LABOR AMONGPHYSIOLOGICAL CHILDBIRTH MOTHERS - Meidayana Refisiliyani; Dewi Nur Anita; Riska Mila Valentina (Lppm Unan, 2026)
Background : Duration of labor is an important indicator in assessing labor progress and the quality of midwifery care. Prolonged labor increases the risk of maternal and neonatal morbidity. Active mobilization during the first stage of labor is a recommended non-pharmacological intervention to support physiological labor progress. This study aimed to analyze the relationship between active mobilization during the first stage of labor and the duration of labor among physiological childbirth mothers at RSUD Puruk Cahu, Murung Raya Regency, Central Kalimantan. Method : This study employed an analytic descriptive design with a cross-sectional approach. A total of 20 physiological labor mothers were selected using consecutive sampling. Data on active mobilization were collected through observation sheets, while labor duration data were obtained from partographs and medical records. Data were analyzed using Chi-Square and Independent t-test with a significance level of α = 0.05. Results : A total of 55% of respondents performed active mobilization during the active phase of the first stage of labor. Most respondents (65%) experienced normal labor duration. Chi-Square analysis showed a significant relationship between active mobilization and labor duration (p = 0.048). The mean labor duration in the active mobilization group was 6.0 hours (SD ±1.1), shorter than in the non-mobilization group at 8.3 hours (SD ±1.4), with a significant difference (p = 0.012). Conclusion : There is a significant relationship between active mobilization during the first stage of labor and labor duration in physiological childbirth. Active mobilization contributes to shortening labor duration and can be recommended as a non-pharmacological intervention in evidence-based midwifery care.